The potential benefits of GPS for small scale fishermen in Malaysia - Mohamed Shaffril, Hayrol Azril; Hamzah, Azimi (Medwell Journals, 2016)
This conceptual study attempts to discover the potential benefits of GPS usage for small scale fishermen in Malaysia. Based on the review of literature and document analyses performed, three main benefits of GPS usage for the small scale fishermen were identified namely to increase their income to strengthen safety aspects and to enhance their technology skills and knowledge. This study has come out with a number of recommendations that can assist the concerned parties in constructing the best strategies to further enhance fisheries technologies usage especially the GPS among the small scale fishermen in Malaysia.